The Influence of Supervision and Organizational Culture on Employee Performance with Employee Commitment as an Intervening Variable at PT. Pegadaian (Persero) Pekanbaru City Branch - Putiviandra, Zahra Egitha; Hendriani, Susi; Roesdi, Rosnelly (CV. Rayyan Dwi Bharata, 2024)
This study aims to determine the influence of supervision and organizational culture on employee performance with employee commitment as an intervening variable at PT. Pegadaian (Persero) Pekanbaru City Branch. The sampling technique used in this research is a saturated sample with a sample size of 50 employees at PT. Pegadaian (Persero) Pekanbaru City Branch. The analysis technique used in this research uses the Structural Equation Modeling (SEM) method with Partial Least Squares (PLS) using Smart-PLS Software version 3.0. The research results show that supervision has a positive and significant effect on commitment. Supervision has no effect on performance. Organizational culture has a positive and significant effect on commitment. Organizational Culture and Commitment have a positive and significant effect on Performance. Commitment is able to mediate the influence of Supervision and Organizational Culture on Performance.